Time to tear down the pyramids? A critique of cascading hierarchies as a policy tool. Issue 2 (9th January 2018) - Olsson, Olle; Roos, Anders; Guisson, Ruben; Bruce, Lena; Lamers, Patrick; Hektor, Bo; Thrän, Daniela; Hartley, Damon; Ponitka, Jens; Hildebrandt, Jakob
Abstract : Cascading, or cascade use, is concept that has many different definitions, but a common theme is a sequential use of resources for different purposes. The cascading concept was first presented in the early 1990s but has become an intensively debated topic primarily in the most recent decade. In the available literature on cascading of wood, there are few studies that discuss policy implementation. As this is currently heavily debated, there is an important gap here that we aim to fill. In this paper, we (a) critically review the conceptual history of cascading and (b) highlight the complexities involved in its implementation in policy frameworks. Originally, cascading was discussed as a broad framework for how society better should manage natural resource flows. In more recent debates on woody biomass however, cascading is often presented as simply a hierarchy, wherein material use of wood should hold priority over energy use of wood. This is partly based on an idea that certain forms of wood utilization are inherently more valuable than others, an assumption that becomes problematic when implemented in policy. In reality, how and for what a certain wood resource is used varies with time and place and historical examples of implementation of hierarchical policy frameworks indicate a high risk of unwanted consequences, such as unstable policy structures and tendencies toward a negotiation economy. Cascading of woody biomass can have benefits from both an economical and environmental perspective. However, cascading systems should emerge bottom‐up, not be imposed top‐down through politically determined hierarchies. WIREs Energy Environ 2018, 7:e279. doi: 10.1002/wene.279 This article is categorized under: Energy and Climate > Economics and Policy Energy Policy and Planning > Economics and Policy Abstract : Cascading and biobased pyramids: should they be implemented into policy? How?